Thought Stopping Techniques to Reduce Social Anxiety - Angela Cynthia Maharani; Najlatun Naqiyah (Department of Guidance and Counseling, FIP, Undiksha, 2022)
The word anxiety is not a new term to talk about nowadays. The community environment is gradually starting to open up to various kinds of mental issues such as depression and anxiety disorders. One of the problems that many adolescents experience is the problem in their social field, and that is the cause why there are a lot of adolescents indicated to have symptoms of social anxiety. Many factors influence the existence of social anxiety that adolescents have, such as pressure from peers, demands from the environment and people around them, the search for identity, experiences with other people and so on. In this article, the researcher will discuss about how social anxiety exists in one of Vocational High School in Surabaya. And how the thought stopping technique can be used to reduce the social anxiety. Thought stopping technique itself has been widely used to reduce anxiety symptoms in individuals. The application of the thought stopping technique will be done by giving individual counselling interventions to some students who have positive symptoms of social anxiety.